A random-phase-assisted ray-tracing technique for wireless channel modeling - Zhu, Houtao (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A random-phase-assisted ray-tracing technique for predicting spatio-temporal wireless channel parameters is presented. A two dimensional-three dimensional (2D-3D) hybrid ray-tracing algorithm is implemented in code for the prediction of channel parameters in outdoor micro- and pico- cellular urban enviornments. Meanwhile, a Random Phase Approach (RPA) is applied in the ray-tracing algorithm. The application of the RPA is intended for two purposes: 1) to account for the effects of inaccurate antenna positions; 2) to predict the range of short-term fading fluctuation. Several measurements carried out in pico-cell enviornments confirm the calculation accuracy of this techinque. It was found that measured fluctuation of path-loss and delay profiles are almost fully confined within the 90% confidence interval, providing that the approach can account for the effects mentioned above. In addition, the conventional verification of path-loss and delay profiles predicted by ray tracing was extended to include the verification of angle-of-arrival (AOA). The demonstrated calculation accuracy in spatial and terporal domain confirms the applicability of authors' technique to analyze system performance in real environments.